Steel framed structures with cross laminated timber infill shear walls and semi-rigid connections - Vogiatzis, Tzanetis; Tsalkatidis, Themistoklis; Avdelas, Aris (International Journal of Engineering and Technology, 2019)
In recent years, hybrid steel-timber structures are seeing an increasing use in modern building construction at a competitive price. Cross-laminated timber (CLT) is a prefabricated multi-layer engineered panel wood product, manufactured by gluing layers of solid-sawn lumber at perpendicular angles. Their orientation results in excellent structural rigidity in both orthogonal directions. CLT construction materials are used not only for flooring systems and roof assemblies, but CLT infill shear walls are also gaining a lot of interest as a promising alternative for sustainable primary lateral load resistance systems. This paper extends the current research background on hybrid steel-timber structures. To achieve that, this work is conducted in such way as to explore the potentiality of incorporating CLT infill shear walls within steel framed structures with semi-rigid connections (STSW). In particular, a three-dimensional finite element model using the general-purpose finite ele-ment program ANSYS is generated herein to study the mechanical behaviour of a single-bay, two storey STSW system with semi-rigid connections. Analytical results show that the presence of CLT infill shear walls can significantly improve the performance of moment-resisting frame systems, for multi-storey buildings. Moreover, it is observed from the extended parametrical study that the STSW systems show better performance when an appropriate plastic moment ratio index is defined.Â Â